2016
DOI: 10.1159/000446268
|View full text |Cite
|
Sign up to set email alerts
|

Potassium: From Physiology to Clinical Implications

Abstract: Background: Potassium (K+) is the major intracellular cation, with 98% of the total pool being located in the cells at a concentration of 140-150 mmol/l, and only 2% in the extracellular fluid, where it ranges between 3.5 and 5 mmol/l. A fine regulation of the intracellular-extracellular gradient is crucial for life, as it is the main determinant of membrane voltage; in fact, acute changes of K+ plasma levels may have fatal consequences. Summary: An integrated system including an ‘interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(86 citation statements)
references
References 21 publications
1
75
0
2
Order By: Relevance
“…As measuring buffers we used 2 mM PB at varying pH (5.8 -8.5) and concentrations of KCl (0, 50, 100, 150 mM) or MgCl 2 (0, 5, 10 mM) (Carl Roth, Germany). The physiological KCl concentration up to 150 mM, 40 which corresponds to the upper c(KCl) used here. The highest c(MgCl 2 )=10 mM used in this study is the threshold concentration observed for collapse of vimentin networks.…”
Section: Experimental Designmentioning
confidence: 99%
“…As measuring buffers we used 2 mM PB at varying pH (5.8 -8.5) and concentrations of KCl (0, 50, 100, 150 mM) or MgCl 2 (0, 5, 10 mM) (Carl Roth, Germany). The physiological KCl concentration up to 150 mM, 40 which corresponds to the upper c(KCl) used here. The highest c(MgCl 2 )=10 mM used in this study is the threshold concentration observed for collapse of vimentin networks.…”
Section: Experimental Designmentioning
confidence: 99%
“…These channels perform a dual crucial role in the TAL: first, they ensure K + recycling to the lumen, essential for salt reabsorption; second, they set a positive transepithelial voltage, that drives paracellular reabsorption of cations. 13,14 Additional Na + reabsorption is driven by the generated electrical field through the paracellular way; moreover, other cations (Ca 2+ and Mg…”
Section: Transcellular and Paracellular Salt Absorption Along The Talmentioning
confidence: 99%
“…Obwohl der Kausalzusammenhang bisher nicht eindeutig bewiesen ist, gibt es eine Reihe von plausiblen Mechanismen, die den Einfluss von Kalium auf die Blutdruckregulation erklären können. Dabei werden v. a. hormonelle Veränderungen, eine sekundäre Natriumretention und eine direkte Wirkung auf die glatte Gefäßmuskulatur diskutiert [6]. Interessant ist in diesem Zusammenhang die Gruppe der Peritonealdialysepatienten, die im Gegensatz zu Hämodialysepatienten in bis zu 35 % der Fälle an einer relevanten Hypokaliämie leiden [7].…”
Section: Hypokaliämie Wird Häufig Unterschätztunclassified